The relationship between Tokopedia Television Advertising Exposure and Exposure to Information by the Group of Peers with willingness access the site Tokopedia.com Among Students - DANIEL EDI KURNIAWAN; Wiwid Noor Rakhmad, M.I.Kom (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Tokopedia is a site selling online with a target segmentation young age as a potential market. Tokopedia has a record of most television advertising spending compared with competitors. Nevertheless Tokopedia traffic levels remained below kompetirornya. Achievement is not directly proportional to the cost of a big promotion became a classic problem to be investigated. The purpose of this study was to assess how much the relationship between exposure to television advertising and exposure information Tokopedia.com by a group of peers with a willingness to access the site Tokopedia.com among students. This type of research is explanatory with quantitative approach using the theory and the theory Ad Exposure Leads Group. The research findings obtained from 60 samples using accidental sampling technique was processed using Pearson Product Moment Correlation analysis to explain the direction and strength of the relationship of each independent variable and the dependent variable. Based on the findings of the data processed by the product moment correlation analysis using SPSS, studies show a link between exposure to television advertising Tokopedia as an independent variable with a willingness to access the site Tokopedia as the dependent variable with the strength of weak ties and the positive direction of the relationship. Using similar data analysis, this research also proved that exposure to information by the peer group as the other independent variables with the willingness to access the site Tokopedia have a positive relationship and the strength of the relationship was. This study shows the results of the study are in accordance with both the theory used to discuss the research results. Conclusions from the study raises a number of practical suggestions include media placement in internet marketing, promotion in the field, and construction of facilities for the target consumer's media campaign.